Mallory-Weiss syndrome during pregnancy - Lino Zamudio, José (2015)
The author presents three cases of the Mallory-Weiss syndrome registered at the Hospital Militar Central, Lima in the last years. All the women were treated medically with good results. The influence of vomiting and hiccup in the etiology of this syndrome is remarked, as well as the importance of an adequate physical and endoscopic examination for the appropriate diagnosis.